Effects of site interactivity and site informativeness on perception of advertisements on social networking sites. - Chua, Benjamin Chun Meng. (2011)
This study aims to understand how site interactivity and site informativeness can impact perception of advertisements (ad affect and ad content) on social networking sites. In a laboratory experiment, 300 participants were asked to view an advertisement on Facebook pages of varying levels of interactivity and informativeness. Results indicate that there is a significant interaction effect between site interactivity and site informativeness. In addition, higher levels of site interactivity and informativeness had the most positive impact on ad perception. Implications for research and practice were also discussed.